Sistem Pakar Mendiagnosa Penyakit Skizofrenia Menerapkan Metode Certainty Factor - Cynthia Silaban; Nelly Astuti Hasibuan (STMIK Budi Darma, 2020)
The development of technology is currently very rapid, so the development of these technologies is very beneficial in all fields including health. In today's case there are a lot of things that are detrimental to others even yourself. Where the case can occur self harm to the loss of level of awareness in controlling emotions. The purpose of this study is to diagnose schizophrenia and provide solutions to the conditions experienced through the application of an expert system. The Certainty Factor method can make diagnosing easier and provide a more accurate diagnosis based on previous events and can be revised again in solving new problems. Based on the results of testing with a comparison between the results of diagnosis the system has the ability to solve problems from patients by getting results so that the system can be said to be feasible to use.